(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2024)
Use of the latest achievements in the field of microcontroller programming, such as the Arduino platform, allows to qualitatively change the educational process, makes it more intense, increases student motivation, and makes it possible to implement an individual approach, which is important. And this, in turn, improves the efficiency and quality of microcontroller programming. The purpose of this study is to propose an effective methodology for using Arduino Atmega 328 microcontrollers for teaching students and evaluate the effectiveness of teaching programming based on the use of Arduino Atmega 328 microcontrollers based on the Kirkpatrick model. The paper presents a broad review of works that consider the interaction of a person and microcontrollers. In addition, the impact of this approach on the process of learning and teaching is being evaluated. More than 95 students took part in this experiment. First, during the semester, students were taught programming using Arduino Atmega 328 microcontrollers, after which they evaluated this learning. The evaluation was carried out at three levels of the Kirkpatrick model [1], and as a result, the second and third levels showed almost the same results with an error of 3 percent. This study concluded that such teaching methodology is very important in the process of student learning. Interaction and collaboration in the field of microcontroller programming has also been used to introduce non-traditional curricula, including courses in robotics as a tool for addressing the social aspects of robotics and artificial intelligence.